Atlantic Multidecadal Oscillation modulates the impacts of Arctic sea ice decline - Li, Fei; Orsolini, Yvan; Wang, Huijun; Gao, Yongqi; He, Shengping (Geophysical Research Letters, 2018)
The Arctic sea ice cover has been rapidly declining in the last two decades, concurrent with a shift in the Atlantic Multidecadal Oscillation (AMO) to its warm phase around 1996/1997. Here we use both observations and model simulations to investigate the modulation of the atmospheric impacts of the decreased sea ice cover in the Atlantic sector of the Arctic (AASIC) by the AMO. We find that the AASIC loss during a cold AMO phase induces increased Ural blocking activity, a southeastward‐extended snowpack, and a cold continent anomaly over Eurasia in December through northerly cold air advection and moisture transport from the Arctic. The increased Ural blocking activity and more extended Eurasian snowpack strengthen the upward propagation of planetary waves over the Siberian‐Pacific sector in the lower stratosphere and hence lead to a weakened stratospheric polar vortex and a negative Arctic Oscillation (AO) phase at the surface in February. However, corresponding to the AASIC loss during a warm AMO phase, one finds more widespread warming over the Arctic and a reduced snowpack over Northern Eurasia in December. The stratosphere‐troposphere coupling is suppressed in early winter and no negative AO anomaly is found in February. We suggest that the cold AMO phase is important to regulate the atmospheric response to AASIC decline, and our study provides insight to the ongoing debate on the connection between the Arctic sea ice and the AO. publishedVersion